2000
DOI: 10.1016/s0165-1889(99)00032-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential savings, factor shares, and endogenous growth cycles

Abstract: The paper analyzes the dynamic properties of the neoclassical one-sector growth model with di!erential savings in the sense of Kaldor}Pasinetti. The economy exhibits unstable steady states and #uctuations if the income distribution varies su$ciently and if shareholders save more than workers. The paper analyzes in detail the dynamics for the case with a "xed proportions technology as well as with a smooth approximation. If the savings propensities di!er by an arbitrarily small amount, the system exhibits topol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
34
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 16 publications
4
34
0
1
Order By: Relevance
“…This is also what occurs in our model (as we shall prove in Section 5). Moreover, in Böhm and Kaas (2000) the authors remark a surprisingly rich occurrence of periods in the cycles, and the same occurs in our model: the rich structure of periodicity regions with cycles of any period and with periodic points in several positions between the L and R regions will be here fully described.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…This is also what occurs in our model (as we shall prove in Section 5). Moreover, in Böhm and Kaas (2000) the authors remark a surprisingly rich occurrence of periods in the cycles, and the same occurs in our model: the rich structure of periodicity regions with cycles of any period and with periodic points in several positions between the L and R regions will be here fully described.…”
supporting
confidence: 80%
“…Recently, a one-dimensional piecewise-linear discontinuous map was considered in the one-sector growth model proposed by Böhm and Kaas in Böhm and Kaas (2000), 5 which is similar to our model. The case in which these authors were interested in corresponds to the one called above of regular dynamics.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, our paper shows the relevance of discontinuous maps to the analysis of financial market dynamics, a rather new field of applied mathematics that has not yet yielded many results. Nevertheless, note that there are already several interesting economic models that feature piecewise-smooth or discontinuous maps, for example, the pioneering works by Day (1982Day ( , 1994; Day and Shafer (1987); Day and Pianigiani (1991), which have also been used recently in Metcaf (2008) and Böhm and Kaas (2000). It is also worth mentioning the works by Hommes (1991Hommes ( , 1995; Hommes and Nusse (1991) and Hommes et al (1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently, it has been proved that this understanding is not always correct. In fact, by introducing constant but different savings propensities out of capital and labor income, the insightful paper by Böhm and Kaas (2000) showed that complex dynamics emerge. 2 These models are of the discrete-time type.…”
Section: Introductionmentioning
confidence: 99%